Cultura de sustentabilidade: um estudo de caso da marca Osklen a partir do design estratégico - Toss, Jane (Universidade do Vale do Rio dos Sinos, 2011)
This research deals with the strategic design in its relation to the theme sustainability, from a case of the brand Osklen, company with headquarters in Rio January and stores in more than 20 countries. It is a company dedicated to the promotion of sustainable products and services, that aims, with that, to raise awareness and provide visibility to issues, projects and partnerships involved in the social, environmental, cultural and economical development. It investigates, from Osklen’s case, how fashion design, agent of knowledge and communication, creates tactics actions of innovation, participating in the process of a culture for sustainability. Thus, the objective of this research is to investigate, from strategic design, the value of the concept sustainability in the fashion product-system, as a competitive strategy adopted in the innovation process. The present research, from this cut, analyzes Osklen fashion industry and its manifestations of communication, its concepts related to its own identity and its proposal to sustainability; in the conjunction of economical, financial, social and environmental results, as Osklen has been a vehicle of information and production of new concepts of fashion and sustainability.
Keywords: Design estratégico; Moda; Sustentabilidade; Strategic design; Fashion; Sustainability; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial